226 RELATIONSHIP OF BODY MASS INDEX WITH AIRWAY MECHANICS AND ADIPOCYTE-RELATED CYTOKINES IN AFRICAN AMERICAN ASTHMATICS. (1st January 2006) - Komakula, S.; Mermis, J.; Khatri, S.; Savill, S.; Haque, S.; Jackson, A. C.; Holguin, F.
Abstract : Introduction: To understand the mechanisms by which obesity is associated with increased risk for asthma, we determined the association of body mass index (BMI) with airway mechanics and exhaled nitric oxide (NO) with adipocyte-related cytokine levels in subjects with moderate to severe persistent asthma. Methods: We recruited patients, who were nonsmokers, with moderate to severe asthma during baseline conditions. Blood samples were obtained from all subjects in a fasting state to determine serum levels of inflammatory markers. The Raw (airway resistance) change in response to a DI (deep inhalation) was measured to determine airway hysteresis. Subsequently, we determined the levels of eNO, spirometry, and FRC. Results: We recruited 34 African American patients with a mean age of 50 years (range 25-68) of which 79% were female. The mean BMI was 34 (range 21-55). Sixty-eight percent were obese and 32% were overweight. Obese participants had higher mean leptin levels (1.72 mg/mL; 95% CI 0.11-2.33) compared to overweight (0.78 mg/mL; 95% CI 0.24-1.33) participants (p < .05). Obese subjects had nonsignificant lower mean levels of adiponectin (308.44 mg/mL; 95% CI 23-385) compared to overweight (331.58 mg/mL; 95% CI 26-405) subjects (p = .64). The mean post-DI Raw was higher in the obese (16.2 cmH2O/L/sec; 95% CI 13-20) compared to overweight (13.0 cmH2O/L/sec; 95% CI 6-20) subjects (p < .05). The log-transformed values of eNO in the obese (2.62 ppb) were lower when compared to overweight (3.31 ppb) participants (p < .05). We found nonsignificant correlations between leptin and log-eNO (r = 2.17, p = .4), and log-eNO and adiponectin (r = .14, p = .4). Conclusions: In moderate to severe asthma, BMI was associated with increased leptin levels, increased Raw after a DI, and eNO. Exhaled eNO levels and airway hysteresis were not associated with adipocyte-related cytokines.